PEMANFAATAN AGILE DEVELOPMENT UNTUK PENGEMBANGAN SISTEM INFORMASI AKADEMIK BRAINFOR ISLAMIC SCHOOL - Akmal Nasution; Mohd. Siddik; Adi Prijuna Lubis (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
Abstract: The development of the world of education and learning in schools was triggered by the development of management and management of these schools. The better the management of the school, the better the development of education in the school concerned. The application of technology in school management and management is mandatory to bring schools to develop in a modern and transparent manner. One important part of the school that must be managed properly is the academic part of the school. All information about teacher data, students, materials and even class schedules should be well documented. This is where the role of technology can be utilized so that the management of academic data is not overlapping, messy, and difficult to manage. The purpose of this research is to develop a brain-for-Islamic school-specific academic system. Making a system that can accommodate and even manage all of the academic data is mandatory if the school wants to develop in a better direction. For this reason, researchers will develop a special academic system for the Brainfor Islamic School. In its development, researchers will use the agile development method as a method in developing the system in order to produce a good academic information system according to school needs.Keywords: academic information system; agile development; brainfor islamic school Abstrak: Perkembangan dunia pendidikan dan pembelajaran dalam sekolah dipicu oleh berkembangnya pengelolaan dan manajemen sekolah tersebut. Semakin baik pengelolaan sekolah maka semakin baik pula perkembangkan pendidikan di sekolah yang bersangkutan. Penerapan teknologi dalam pengelolaan dan manajemen sekolah menjadi hal yang wajib untuk membawa sekolah berkembang secara modern dan transparan. Salah satu bagian penting dalam sekolah yang harus di kelola dengan baik adalah bagian akademik sekolah. Semua informasi tentang data guru, siswa, materi dan bahkan jadwal pelajaran seharusnya terdokumentasi dengan baik. Disinilah peran teknologi dapat dimanfaatkan agar pengelolaan data akademik tersebut tidak tumpang tindih, berantakan, dan sulit dikelola. Tujua penelitin ini untuk mengembangakan sebuah sistem akademik khusus sekolah brainfor islamic school. Pembuatan sebuah sistem yang dapat menampung bahkan mengelola semua data akademik tersebut menjadi wajib jika ingin sekolah berkembang kearah yang lebih baik lagi. Untuk itu peneliti akan mengembangkan sebuah sistem akademik khusus bagi sekolah Brainfor Islamic School. Dalam pengembangnannya, peneliti akan menggunakan metode agile development sebagai metode dalam pengembangan sistem tersebut guna menghasilkan sebuah sistem informasi akademik yang baik sesuai dengan kebutuhan sekolah.kata kunci: sistem informasi akademik; agile development; brainfor islamic school